Copper-catalyzed arylation of polycyclic aromatic hydrocarbons by the PO group. Issue 93 (11th November 2020) - Niu, Yuan; Qi, Zhichao; Lou, Qinxin; Bai, Pengbo; Yang, Shangdong
Abstract : Copper-catalyzed regioselective arylation of polycyclic aromatic hydrocarbons (PAHs) with potential fluorescence properties by the PO group has been performed. Abstract : The first example of a directed and regioselective arylation of polycyclic aromatic hydrocarbons (PAHs) by using a PO directing group is reported herein. The protocol uses a cheap copper catalyst, and results in a breakthrough meta -selective C–H functionalization of arylphosphine oxide compounds. Substrates with potential fluorescence properties, for example, pyrene and fluoranthene, were successfully arylated under the system, thus achieving an efficient modification of fluorescent molecules containing the PO functional group.